Proceedings of the ACM Workshop on Automotive Cybersecurity 2019
DOI: 10.1145/3309171.3309180
|View full text |Cite
|
Sign up to set email alerts
|

Towards a CAN IDS Based on a Neural Network Data Field Predictor

Abstract: Modern vehicles contain a few controller area networks (CANs), which allow scores of on-board electronic control units (ECUs) to communicate messages critical to vehicle functions and driver safety. CAN provides a lightweight and reliable broadcast protocol but is bereft of security features. As evidenced by many recent research works, CAN exploits are possible both remotely and with direct access, fueling a growing CAN intrusion detection system (IDS) body of research. A challenge for pioneering vehicle-agnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In 2019, Pawelec et al [26] proposed a 3-layer LSTM neural network to predict the data payload for each CAN ID, which avoided reverse engineering proprietary encoding. Similarly, Qin et al [12] also implemented anomaly detection for CAN bus based on timing features by LSTM and re-considered two data formats of CAN frames.…”
Section: Intrusion Detection Model Based On Deep Learningmentioning
confidence: 99%
“…In 2019, Pawelec et al [26] proposed a 3-layer LSTM neural network to predict the data payload for each CAN ID, which avoided reverse engineering proprietary encoding. Similarly, Qin et al [12] also implemented anomaly detection for CAN bus based on timing features by LSTM and re-considered two data formats of CAN frames.…”
Section: Intrusion Detection Model Based On Deep Learningmentioning
confidence: 99%
“…Jichici et al 46 evaluate the possibilities for integrating the NN‐based IDS on automotive‐grade embedded platforms, and the experiment results show that this task is quite challenging due to large requirement of memory size and computational power. Pawelec et al 47 test the effectiveness of employing DNN to predict CAN message at the bit level, which would offer the IDS capability but avoiding reverse engineering proprietary encodings of CAN messages. Kuwahara et al 48 study the applicability of statistical anomaly detection methods to identify malicious CAN messages, where a pipeline technology is proposed to extract the timestamp and ID information in each messages quickly, and the efficiency of the proposed method is evaluated in real message datasets and in supervised and unsupervised cases.…”
Section: The State‐of‐the‐art Work About Security Protection Of In‐vehicle Networkmentioning
confidence: 99%
“…In parallel, CAN defensive security research is growing quickly; we found 15 surveys of the area since 2017, e.g., [23,24], with over 60 works on CAN intrusion detection between 2016-19. Yet these works are impeded by obfuscated CAN data, forced to either use side-channel methods that ignore message contents [25][26][27], use black-box methods ignorant of message meanings [28][29][30], or either arduously reverse engineer a few signals for a specific vehicle [31] or rely on an OEM for signal definitions [32], which keeps CAN security in the OEM's hands and develops per-make (not vehicle-agnostic) capabilities. A vehicle-agnostic CAN signal reverse engineering tool promises to remove these limitations and provide rich, online, time-series data for advancements in detection and other security technologies.…”
Section: Impactmentioning
confidence: 99%